Pemanfaatan Micro-Influencer sebagai Strategi Publik Relations dalam UMKM - Elvira Hilwa Salsabila; Rizki Suheldi; Mira Andani; Nurwelis Nurwelis; Diki Wahyudi; Muhammad Rahmatul Burhan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
New influencers have emerged as part of the field of public relations as a result of technological advances. Communication with influencers on social media is the main focus for strategic communication. The development of Micro, Small and Medium Enterprises (MSMEs) is increasing day by day. Research data collection techniques using secondary data are information obtained or collected data by scientists from various existing sources such as obtained from important documents, websites, books research results in choosing micro-influencers as a marketing medium, it is recommended to consider micro-influencers with attractive attractive characteristics, micro- influencers with quality expertise characteristics, and micro-influencers with trustworthy trust characteristics. By considering these three characteristics in choosing micro-influencers as a marketing medium, it is hoped that in the future it will be able to increase the formation of consumer attitudes towards good brands which can simultaneously increase buyer interest. Micro-influencers as a Public Relations Strategy in MSMEs is a strategic marketing method because many entities have recognized social media influencers as relevant intermediaries, especially because they have the ability to connect with stakeholders that are difficult to reach, such as niche markets or teenage and adult consumers.